2018
DOI: 10.1002/hpja.181
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of rescuing people who have driven into floodwater: Understanding challenges and identifying areas for providing support

Abstract: We propose five strategies for translating these results into practice, including: training and protocol development for (i) emergency personnel and (ii) telephone operators; (iii) training for rescuers regarding non-compliant rescuees; (iv) educating the public and (v) increasing compliance with closed roads. Current findings provide valuable insights into how rescuers can be supported in performing their roles, and implementation of these strategies has the potential to reduce fatalities occurring due to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Qualitative research should also be undertaken to explore motivations for undertaking rescues and any ongoing effects after performing the rescue as has been done with those who have rescued people who have driven through floodwaters. 52 Although country of birth was not found to impact past experience of having undertaken a rescue, special consideration is required among culturally and linguistically diverse (CALD) communities. This includes ensuring awareness of the hazards and risks presented by different aquatic environments, as well as improving swimming and water safety skills among these communities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research should also be undertaken to explore motivations for undertaking rescues and any ongoing effects after performing the rescue as has been done with those who have rescued people who have driven through floodwaters. 52 Although country of birth was not found to impact past experience of having undertaken a rescue, special consideration is required among culturally and linguistically diverse (CALD) communities. This includes ensuring awareness of the hazards and risks presented by different aquatic environments, as well as improving swimming and water safety skills among these communities.…”
Section: Resultsmentioning
confidence: 99%
“…As rescue and resuscitation are secondary and tertiary prevention measures, work around primary prevention will be required to reduce the overall burden of drowning. Qualitative research should also be undertaken to explore motivations for undertaking rescues and any ongoing effects after performing the rescue as has been done with those who have rescued people who have driven through floodwaters 52 …”
Section: Implications For Public Healthmentioning
confidence: 99%
“…This study identified non-aquatic transport incidents (driving into floodwater) as the leading activity accounting for 41% of all deaths. Multiple prevention strategies have been suggested for preventing people driving into floodwaters [13,17,21,23], however for child drowning, the responsibility lies with the parents or caregivers (as drivers of the vehicle) and therefore such strategies must influence their decision making. Use of a health protection model [43] may be valuable when considering appropriate strategies; as similar approaches to discouraging the behavior of driving into floodwaters have appealed to drivers to consider the risk to their own life, that of their passengers and rescuers [21].…”
Section: Risks Of Driving Into Floodwatersmentioning
confidence: 99%
“…While previous bodies of research associated with floods have focused on the overall epidemiology [13][14][15], behavioral research associated with driving into floodwaters [16][17][18][19][20], and issues impacting rescuers [21]-as well as community experiences [22], perceptions [23], response and resilience [24,25]-few studies have specifically examined the epidemiology and circumstances associated with child drowning during times of flood. A study in Bangladesh identified a strong association between the annual monsoon season and child drowning of those aged 1-4 years in Matlab, Bangladesh [26].…”
Section: Introductionmentioning
confidence: 99%
“…Driving into floodwaters is a leading activity immediately prior to flood-related drowning, a fact that has been highlighted in a number of countries (Diakakis & Deligiannakis, 2013, 2017Fitzgerald, Du, Jamal, Clark, & Hou, 2010;Franklin, King, Aitken, & Leggat, 2014;Gissing, Haynes, Coates, & Keys, 2016;Hamilton, Peden, Keech, & Hagger, 2016;Hamilton, Peden, Pearson, & Hagger, 2016;Hamilton, Price, Keech, Peden, & Hagger, 2018;Haynes et al, 2017;Keech, Smith, Peden, Hagger, & Hamilton, 2019;Pearson & Hamilton, 2014;Peden et al, 2017;Pereira, Diakakis, Deligiannakis, & Zêzere, 2017;Salvati, 2018;Freddy Vinet, Boissier, & Saint-Martin, 2016).…”
Section: Introductionmentioning
confidence: 99%